Chance of a lifetime - Deveraux, Jude; Sheets, Tara, 1973- (Mira, 2020)
"In 1840s Ireland, heartstruck thief Liam O'Connor lures away lovely Cora from her intended, so angels send him to small-town contemporary America to right this wrong. He must convince today's Cora, a police detective, to marry a lawyer she loves, or Liam will be damned for eternity." - Provided by publisher.
In English.
Keywords: Time travel -- Fiction; Magic -- Fiction; Policewomen -- Fiction; Outlaws -- Fiction; Man-woman relationships -- Fiction; Ireland -- Fiction; Romance fiction; Science fiction